The form and content of modern english music and its application as a teaching tool in the classroom - Ambuludi Pardo, Paola Karina (2012)
The present research is about The Form and Content of Modern English Music and its Application as a Teaching Tool in the Classroom. It was carried out in Loja, in La Pradera and Yahuarcuna neighbourhoods. The sample population was young people from 15 to 21 years old. To achieve the proposed goals was necessary to make a bibliographical research in books and in internet and a field research using surveys in order to obtain information about popular music and its uses as a teaching tool in class.